UPACARA ADAT TULUDE PADA MASYARAKAT TAHUNA KEPULAUAN SANGIHE - Dwi Abrianto Matteuw (HOLISTIK, Journal of Social and Culture, 2023)
Culture is a reflection of human habits both individually and in groups or communities, culture is formed so as to build its own characteristics of the community. Traditional ceremonies are a series of traditional activities carried out for generations that have meaning and purpose in them. The traditional Tulude ceremony is one of the traditional cultures that is still maintained, fostered and developed by the people of Sangihe Islands Regency to this day. The traditional Tulude ceremony is also a traditional communication medium that contains expressions of gratitude to God as a form of His maintenance and participation in the life of the Sangihe community, which contains ethical, moral, and religious values. This traditional Tulude ceremony is carried out with the intention of asking for protection and thanking God's blessings and gifts in the past year and the new year. Tulude traditional ceremonies have become an obligation to be carried out every year, precisely on the 31st of January, the implementation of Tulude traditional ceremonies has a religious nature. The stages of the Tulude traditional ceremony began with the Salo Dance to honor the government and the community, and became the culmination of the implementation, namely the cutting of the traditional Tamo cake and what remains a moment of togetherness, namely the people's feast. Tamo traditional cake in Tulude traditional ceremony symbolizes unity and unity between Sangihe people. Keywords : traditional ceremony, tulude, tamo cake